Level of implementation of the pharmacovigilance program and its associated factors in health institutions in Valle del Cauca - Castro Espinosa, Jobany; Estupiñán Cabrera, Hernán; Gil Pineda, María Alejandra; Moreno Posso, Laura Valentina; Donoso Huertas, María Cristina; Pino Quinto, Daihana (Revista colombiana de ciencias químico-farmacéuticas, 2024)
Introduction: pharmacovigilance programs monitor the Adverse Drug Events (ADEs). Although Colombian legislation mandates healthcare service providers to have an institutional pharmacovigilance program, not all institutions comply with this regulation. Objective: Determine the level of implementation of the pharmacovigilance program and its associated factors in health institutions in Valle del Cauca. Methodology: A survey was designed based on the HENRI PFv scale of the National Institute for Food and Drug Surveillance (INVIMA). The survey was sent to health institutions. Information was consulted in the special registry of health providers and information on the EAM report in VigiFlow. The association between the implementation of the program and each of the factors was evaluated, using Stata version 14 software. Results: 80 institutions participated, of which 81% were classified as being implemented and 19% as not being implemented. The item with the lowest compliance was having pharmacovigilance programs and strategies (40%) and having a quality management system (45%), and the item with the highest compliance was the review of alerts and health measures (88%). The bivariate analysis allowed establishing the association between program implementation and variables such as the presence of pharmaceutical personnel, the institution’s location in a large municipality, the program’s operational duration of more than one year, and the perception that INVIMA does not send reports to stakeholders. Conclusion: The implementation was determined for each institution. The factors associated with implementation constitute aspects to consider to improve the functioning of pharmacovigilance programs. Introducción: Los Eventos Adversos Medicamentosos (EAM), son vigilados por los programas de farmacovigilancia. Aunque en Colombia la legislación exige a las instituciones prestadoras de servicios de salud contar con un programa institucional de farmacovigilancia, no todas las instituciones cumplen esta regulación. Objetivo: Determinar el nivel de implementación del programa de farmacovigilancia y sus factores asociados en instituciones de salud del Valle del Cauca. Metodología: Se diseñó una encuesta basada en la escala HENRI PFv del Instituto Nacional de Vigilancia de Medicamentos y Alimentos (INVIMA). La encuesta se envió a las instituciones de salud. Se consultó información en el registro especial de prestadores de salud e información sobre el reporte en VigiFlow. Resultados: Participaron 80 instituciones de las que el 81% catalogaron como en implementación y el 19% como no implementado. El ítem de menor cumplimiento fue contar con programas y estrategias de farmacovigilancia (40%) y contar con un sistema de gestión de calidad (45%) y el item de mayor cumplimiento fue la revisión de alertas y medidas sanitarias (88%). El análisis bivariado permitió establecer la asociación entre la implementación del programa y variables como la presencia de personal farmacéutico, la ubicación de la institución en un municipio grande, la duración del funcionamiento del programa de más de un año, y la percepción de que el INVIMA no envía reportes a los actores. Conclusión: Se determinó la implementación para cada institución. Los factores asociados a la implementación constituyen aspectos a considerar para mejorar el funcionamiento de los programas de farmacovigilancia. Introdução: Os Eventos Adversos Medicamentosos (EAM), são vigiados pelos programas de farmacovigilância. Embora na Colômbia a legislação exija que as instituições prestadoras de serviços de saúde contem com um programa institucional de farmacovigilância, nem todas as instituições cumprem esta regulamentação. Objetivo: Determinar o nível de implementação do programa de farmacovigilância e seus fatores associados nas instituições de saúde do Vale do Cauca. Metodologia: Foi desenvolvida uma consulta baseada na escala HENRI PFv do Instituto Nacional de Vigilância de Medicamentos e Alimentos (INVIMA). A consulta foi enviada às instituições de saúde. Foram consultadas informações no registro especial de discussão de saúde e informações sobre o relatório no VigiFlow. Resultados: Participaram 80 instituições das quais 81% foram catalogadas como em implementação e 19% como não implantadas. O item de menor cumprimento foi contado com programas e estratégias de farmacovigilância (40%) e contado com um sistema de gestão de qualidade (45%) e o item de maior cumprimento foi a revisão de alertas e medidas sanitárias (88%). A análise bivariada permitiu estabelecer a associação entre a implementação do programa e variáveis como a presença de farmacêutico pessoal, a localização da instituição em um município grande, a duração do funcionamento do programa por mais de um ano, e a percepção de que o INVIMA no envía reporta aos atores. Conclusão: Foi determinada a implementação para cada instituição. Os fatores associados à implementação constituem aspectos a serem considerados para melhorar o funcionamento dos programas de farmacovigilância.